THE IMBALANCE OF NATURAL WATER AND ECOLOGICAL BALANCE OF GEOLOGICAL ENVIRONMENT IN SOUTHERN UKRAINE AND ITS ECOLOGICAL CONSEQUENCES - Baysarovych, I.; Yakovlev, E. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Factors of influence of anthropogenic changes on geological environment of Southern Ukraine and their impact on regional natural water and ecological balance have been considered. Regulated flow, water industry activity including abstraction of water into water deficiency region by means of chanals have led to substantial reduction of suspended matter and decreasing of Dnieper water quantity coming in the Black Sea. As a result of named factors, the natural water and ecological conditions of the region were disturbed.